2018
DOI: 10.3389/fmicb.2018.02886
|View full text |Cite
|
Sign up to set email alerts
|

Two Modes of Riboflavin-Mediated Extracellular Electron Transfer in Geobacter uraniireducens

Abstract: Anaerobes respire extracellular electron acceptors by extracellular electron transfer (EET). It is widely recognized that flavins can act as electron shuttles to facilitate this process. Flavin synthesis genes are widely distributed in Geobacter species. However, the functions of flavins in the EET of Geobacter species are unclear. Here, we demonstrate that G. uraniireducens can secrete abundant riboflavin (up to 270 nM) to facilitate EET. When an electrode was used as the electron acceptor, the quick recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Geobacter species can use different mechanisms for metal ion reduction and for current generation. In addition, it has been shown that an efficient Fe(III) oxide reduction did not mean the same efficient current generation in Geobacter species and vice versa (Huang et al, ; Rotaru et al, ; Tan et al, ). In particular, G. sulfurreducens used different ways to respire Fe(III) oxide and anode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Geobacter species can use different mechanisms for metal ion reduction and for current generation. In addition, it has been shown that an efficient Fe(III) oxide reduction did not mean the same efficient current generation in Geobacter species and vice versa (Huang et al, ; Rotaru et al, ; Tan et al, ). In particular, G. sulfurreducens used different ways to respire Fe(III) oxide and anode.…”
Section: Discussionmentioning
confidence: 99%
“…Fe(III) reduction could have been an important process on early Earth that drives microbial evolution. In particular, Geobacter species have evolved different ways to respire Fe(III) oxides over billions of years (Holmes et al, ; Huang et al, ). Even under laboratory conditions, Geobacter species have shown adaptive evolution to efficiently reduce Fe(III) oxides (Smith et al, ; Summers et al, ; Tremblay et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can transfer electrons to the mineral surface by direct contact or by using flavins [e.g., flavin mononucleotide (FMN) and riboflavin] as extracellular electron shuttles (von Canstein et al, 2008; Shi et al, 2016). The latter approach has been shown to be faster for reduction of Fe(III) (hydr)oxides (von Canstein et al, 2008; Ross et al, 2009; Huang et al, 2018). FMN and riboflavin as extracellular electron shuttles can be secreted by many bacteria (such as Shewanella oneidensis strain MR-1, Shewanella decolorationis strain S12, and Geobacter sulfurreducens ) (von Canstein et al, 2008; Kotloski and Gralnick, 2013; Okamoto et al, 2014; Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The debate on the composition of nanowires and their role in long-range electron transfer continues. Moreover, self-secreted flavins contribute to Geobacter EET as cofactors by binding to outer membrane c -Cyts when electrodes are used as electron acceptors ( Okamoto et al, 2014a ; Okamoto et al, 2014b ; Huang et al, 2018 ; Thirumurthy and Jones, 2020 ). Based on these studies, two microbial EET pathways have been proposed: direct EET via c -Cyts or electrically conductive nanowires and indirect EET via exogenous or endogenous electron shuttles.…”
Section: Extracellular Electron Transfer Of Geobacter and Shewanella : Biofilm Vs Planktonic Exoelementioning
confidence: 99%